MODERN PHYSIOTHERAPEUTIC MANAGEMENT IN WOMEN WITH BREAST CANCER TREATED WITH BCT - A REVIEW ARTICLE - Piotr Kaczmarek, (International Journal of Innovative Technologies in Social Science, 2025)
Breast carcinoma maintains its status as the most frequently diagnosed malignancy among women globally, with epidemiological data demonstrating the registration of over 2.3 million new cases annually. This trend is characterized by a persistent and concerning increase in incidence rates across various demographic strata. Consequently, optimizing both oncological efficacy and the subsequent quality of life (QoL) has become a primary focus in clinical oncology.Among the established therapeutic modalities for localized breast cancer, Breast-Conserving Therapy (BCT)—typically involving lumpectomy or partial mastectomy followed by adjuvant radiotherapy—has achieved substantive clinical ascendancy and is now frequently regarded as the standard of care for early-stage disease. This preference is driven by robust Level I evidence indicating oncological outcomes non-inferior to radical mastectomy, coupled with superior patient-reported outcomes (PROs) concerning body image and psychological well-being.The widespread adoption of this conservative surgical paradigm has generated a corresponding and significant surge in the volume of patients who require comprehensive, evidence-based rehabilitation following their primary treatment course. Despite its minimally invasive nature relative to mastectomy, BCT is frequently associated with long-term functional sequelae. These morbidities can encompass a restricted range of motion (ROM) of the ipsilateral shoulder, the development of lymphedema, chronic neuropathic or myofascial pain syndromes, and generalized functional decline.In this context, specialized physiotherapeutic intervention becomes an indispensable component of the continuum of care. The structured implementation of rehabilitation protocols aims to mitigate these potential complications, restore optimal biomechanical function, and ultimately, enhance the overall QoL and long-term functional status of the patient population.The aim of the current paper is to critically present and analyze the latest contemporary approaches and methodological advancements in the field of physiotherapy. This exploration focuses specifically on their application in improving the functional outcomes and addressing the complex physical morbidities encountered in patients who have undergone BCT.